High-strength nano composite screw material based on concentric fiber cylinder structure and preparation method of high-strength nano composite screw material
By using a combination process of concentric fiber cylinder structure and GO/HA nanofillers in fracture repair materials, the problems of poor mechanical strength and insignificant osteogenic activity of existing bone repair materials are solved, and the screw materials that are high-strength and promote bone performance are achieved, meeting the complex use needs.
Patent Information
- Application Number
- CN202411302247.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-09-18
Smart Images

Figure CN119524221A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation technology of a bone repair material, and in particular to a high-strength nano-composite screw material based on a concentric fiber tube structure and a preparation method thereof. Background Art
[0002] Screws are internal fixation devices that can be used to fix fracture sites. They are generally used alone or in combination with bone plates in clinical practice. Metal screws are currently the most commonly used materials, but due to stress shielding, the need for secondary surgery, and the susceptibility to inflammation, patients may experience discomfort or a huge physical / psychological burden during use. In response to the shortcomings of current metal materials, scientists have developed a variety of new degradable screw materials in recent years, such as hydroxyapatite screws and polylactic acid screws, which can be degraded in the body after implantation, effectively reducing the pain caused to patients by secondary surgery. Since the development of degradable screws is still in its early stages, related technologies are not yet mature. Problems such as the brittle fracture of hydroxyapatite screws and the lack of significant biological activity of polylactic acid screws still need to be urgently addressed.
[0003] In view of the above problems, the present invention is inspired by the tree ring structure: after the tree is felled, many concentric rings can be seen on the stump, which are called annual rings in botany. Annual rings are formed by trees during their growth process under the influence of seasons, and one ring is produced per year. Due to the existence of the annual ring structure, the bending strength of trees is very excellent and can resist effects such as strong winds. Therefore, if this structure is introduced into the screw, can it be enhanced? Secondly, hydroxyapatite has a very good effect on promoting osteogenesis, but because it is easy to agglomerate and is not well dispersed in the polymer matrix, the amount of its nanocomposite addition is limited. GO, as a new type of nanofiller containing a large number of oxygen-containing functional groups on the surface, has good dispersibility in water, and a large number of oxygen-containing functional groups can serve as sites for the nucleation of hydroxyapatite. Therefore, if GO can be used as the core and hydroxyapatite can be compounded on its surface to prepare a new nanofiller with high dispersibility and osteogenic activity, it will have a huge driving effect on the functional upgrading of the screw.
[0004] Therefore, the present invention proposes a high-strength nanocomposite screw material based on a concentric fiber cylinder structure and a preparation method thereof. By preparing a fiber cylinder with a concentric structure to simulate the structure of concentric growth rings, and preparing GO / HA nanofillers at the same time, the screw is strengthened and endowed with osteogenic activity, providing a new strategy for the upgrade of the screw. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength nanocomposite screw material based on a concentric fiber tube structure and a preparation method thereof in view of the problems of poor mechanical strength and insignificant osteogenic activity of traditional bone repair hydrogels.
[0006] The present invention is implemented by the following technical solutions:
[0007] A method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure, comprising:
[0008] 1) firstly weave polylactic acid-co-glycolic acid (PLGA) fiber cylindrical materials with different diameter gradients;
[0009] 2) using an in-situ mineralization process to mineralize hydroxyapatite on the surface of graphene oxide (GO) to obtain GO / HA nanofillers, and using a freeze-blasting method to prepare an alkali-soluble chitosan / cellulose mixed solution composited with GO / HA, and degassing by low-speed centrifugation;
[0010] 3) Fiber cylinders of different diameters are concentrically arranged and fixed in an open cylindrical mold, the above solution is poured against the wall, and the mold is transferred together with the fiber cylinders to 60-80°C for in-situ gelation;
[0011] 4) After dialysis, the material is transferred to a rotary drying device for drying and dehydration, and the desired high-strength nano-composite screw material is obtained after turning according to the drawing.
[0012] Furthermore, in the step 1), the diameter of the fiber cylinders is 3-49 mm, and they are arranged at equal intervals from small to large, and the number of the fiber cylinders is 3-15.
[0013] Further, in the step 2), the in-situ mineralization process is to add GO to the surface mineralization solution, the diameter of GO is about 3-6 microns, and the concentration is 0.01-0.08wt%; the surface mineralization solution formula is: sodium chloride 50-70mM, disodium hydrogen phosphate 20-30mM, potassium chloride 60-100mM, potassium hydrogen phosphate 5-10mM, magnesium sulfate 0.4-0.75mM, magnesium chloride 0.8-1.2mM, calcium chloride 4-6mM, sodium bicarbonate 0.2-0.4mM, dicalcium hydrogen phosphate 0.4-0.6mM, sodium sulfate 0.025-0.05mM, HEPES13-25mM, and the solvent is deionized water; the mineralization temperature is 35-37°C, the mineralization time is 1-7 days, and the stirring rate is 30-60r / min;
[0014] Furthermore, the formula of the alkali-soluble chitosan / cellulose solution is: the total concentration of chitosan and cellulose is 4-10wt%, GO / HA is 0.5-10wt%, urea is 5-7wt%, lithium hydroxide monohydrate is 7-10wt%, and the rest is deionized water, wherein the molecular weight of chitosan is 1-2 million, the degree of deacetylation is 70-80%, and the cellulose is 1-2 million. The freezing-explosion method is to stir and swell the solution for 30-60 minutes, freeze it at -20--80℃, and then chisel it until the ice is completely melted. The above process is repeated 3-5 times to obtain a completely dissolved alkali-soluble chitosan / cellulose mixed solution; low-speed centrifugal degassing process: the speed is 1000-1500rpm, and the time is 5-15min.
[0015] Furthermore, in the step 3), the diameter of the open cylindrical mold is 2-5 cm, the height is 5-10 cm, a hook is provided on the lower base for fixing the lower end of the fiber tube, and a bracket is provided on the upper end for fixing the upper end of the fiber tube; the in situ gelation time is 1-3 hours, and deionized water is added to the gel at intervals of 30 minutes during the gelation process.
[0016] Furthermore, the structure of the rotary drying equipment in step 4) is as follows: the heating and drying components are two parallel and juxtaposed heating screws that can rotate in opposite directions, and the two screw bodies are provided with stainless steel cylinders with fine holes. The screw speed is 20-50r / min, and the heating temperature is 50-80°C.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] 1) The present invention uses chitosan, cellulose, GO, HA, PLGA fibers and the like as raw materials, and combines fiber weaving, in-situ casting, thermal gelation, nanocomposite, rotary drying and turning to prepare a high-strength nanocomposite screw material based on a concentric fiber tube structure. The above raw material selection and process combination are original to the present invention.
[0019] 2) The present invention introduces nanocomposite and wood-like concentric growth ring reinforcement strategies. First, GO is used as the core to in-situ mineralize the HA layer on its surface to obtain GO / HA nanofiller, which retains the high dispersibility of GO in water; when the GO / HA nanofiller is compounded into the chitosan / cellulose matrix, the polymer matrix can be reinforced. On the other hand, a fiber cylinder with a concentric structure is used to evenly fix the fiber cylinder in the polymer matrix through an in-situ casting process to form a wood-like concentric growth ring structure for reinforcing the screw; wherein the fiber cylinders with different radii are fixed in the mold to form a concentric structure similar to the growth ring, and when the solution is poured, the solution penetrates into the fiber cylinder, and after gelation, good penetration and mechanical bite are formed. When the screw is subjected to bending stress, the nanocomposite filler reinforces the entire matrix, and when the internal concentric fiber cylinder begins to deform in the polymer matrix, the fiber pull-out reinforcement mechanism is used to suppress the development of cracks, thereby achieving the purpose of reinforcing the screw. The above-mentioned upward punching reinforcement strategy is the first of its kind in the present invention.
[0020] 3) The present invention adopts an open cylindrical mold + a fiber cylinder fixed arrangement technology + an in-situ casting and curing process at the same time to realize a nano-composite screw material with a concentric fiber cylinder structure. Since the present invention designs a concentric fiber cylinder structure, an open cylindrical mold is introduced to fix the upper and lower ends of the fiber cylinder, so that it can be fixedly arranged according to the diameter size, laying the foundation for the subsequent formation of a wood-like concentric annual ring structure; then, through the in-situ casting process, the chitosan / cellulose solution is poured into the mold against the wall, and the mold is completely filled through the flow and penetration of the solution, while the fiber cylinder is wrapped around by the polymer solution, and the fixed arrangement of the fiber cylinder will not be destroyed; finally, under the action of the heating in-situ curing process, the polymer solution is successfully gelled to obtain the first stage morphology of the screw. According to the structure of the composite screw and the actual preparation needs, the present invention carefully designs the above-mentioned combined process, realizes the new application of the old process, and finally obtains the required composite screw.
[0021] 4) The present invention combines the combined processes of in-situ pouring gelation + rotary drying + turning, so that the screw undergoes three forms of hydrogel-rod-screw in turn, and finally obtains the required high-strength nano-composite screw material based on the concentric fiber tube structure. First, through the in-situ pouring gelation process, a composite hydrogel material with a fixedly arranged fiber cylinder embedded inside is obtained; through rotary drying, the moisture inside the gel is gradually removed, and at the same time, the special rotary drying device in the present invention can ensure that the moisture on the surface of the hydrogel is evenly removed, so that the obtained composite rod remains straight. If the hydrogel is directly dried, a curved rod will be obtained, which cannot be subsequently turned; finally, the present invention combines the traditional turning process to form the required threaded structure on the surface of the straight rod, and finally forms the required composite screw material. It is the organic synergy of the above-mentioned combined processes that enables the screws required by the present invention to be successfully prepared. Behind the seemingly simple process is the applicant's careful coordination and cooperation of the material structure and the preparation process, realizing the new application of the combination of traditional processes.
[0022] 5) The screws in the present invention have high biocompatibility, biodegradability, high bending strength, and osteogenic properties, meeting the complex use requirements of screws. The raw materials used in the present invention are all highly biocompatible and biodegradable, so the composite screws are non-toxic during subsequent use, and can be degraded in the body, thereby helping patients get rid of the trouble of secondary surgery; the nano-composite and the wood-like concentric annual ring structure controllably constructed using fiber cylinders enhance the screws, so that the screws have excellent bending strength, meeting the mechanical requirements of the screws when used in the body; and in the present invention, GO is used as the core, and the HA coating is in situ mineralized on its surface to form a GO / HA nanofiller. Due to the high dispersibility of GO in water, the amount of GO / HA added can be significantly improved compared to HA, which is closer to the HA content of natural bone, showing excellent osteogenic properties. It is precisely because of the organic synergy between the above functions that the composite screws can meet complex usage scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the preparation process of high-strength nanocomposite screw materials based on concentric fiber tube structure. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific examples. Figure 1As shown, it is a schematic diagram of the preparation process of the screw material of the present invention. In a specific implementation mode, the working process of the rotary drying device is: two heatable screws are at the bottom, and the screws can rotate; then a stainless steel cylinder with fine holes is placed above the two screws and parallel to the screws, and the sample is placed inside the stainless steel cylinder parallel to the direction of the stainless steel cylinder. The stainless steel cylinder is driven by the rotation of the screws, and the fine holes on the stainless steel cylinder are used for water vapor discharge.
[0025] Comparative Example 1:
[0026] 1) An in-situ mineralization process was used to mineralize hydroxyapatite on the surface of GO to obtain GO / HA nanofiller, wherein the mineralization solution was: 50 mM sodium chloride, 30 mM disodium hydrogen phosphate, 100 mM potassium chloride, 5 mM potassium hydrogen phosphate, 0.6 mM magnesium sulfate, 0.9 mM magnesium chloride, 5 mM calcium chloride, 0.2 mM sodium bicarbonate, 0.4 mM dicalcium hydrogen phosphate, 0.05 mM sodium sulfate, 18 mM HEPES, and the solvent was deionized water; the mineralization temperature was 37 ° C, the mineralization time was 3 days, and the stirring rate was 30 r / min. At the same time, a freeze-explosion method was used (the solution was stirred and swelled for 30 minutes, then placed at -20°C for freezing, and then ice was chiseled until the ice was completely melted, and the above process was repeated 4 times) to prepare an alkali-soluble chitosan / cellulose mixed solution composited with GO / HA (the solution contained 4wt% chitosan, 4wt% cellulose, 0.8wt% GO / HA, 6wt% urea, 8wt% lithium hydroxide monohydrate, and the rest was deionized water, wherein the molecular weight of chitosan was 1 million, the degree of deacetylation was 80%, and the molecular weight of cellulose was 1.8 million), and low-speed centrifugation (speed of 1000rpm, time of 5min) was used for degassing;
[0027] 2) Pour the above solution into the mold and transfer it together with the mold to 60°C for in-situ gelation (the in-situ gelation time is 2 hours, and deionized water is added to the gel every 30 minutes during the gelation process);
[0028] 4) After the deionized water dialyzate is completely used, the product is transferred to a rotary drying device (the heating and drying components of which are two parallel and counter-rotating heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying and dehydration (the screw speed is 30 r / min, and the heating temperature is 60°C). After turning according to the drawing, the desired high-strength nano-composite screw material is obtained.
[0029] First, the extract of the above material was prepared and co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 7 days. The CCK-8 results showed that the cell survival rate was about 92.8% and the bending strength of the screw was about 224.6MPa. After the material was co-cultured with BMSCs for 14 days, ALP was detected and the results showed that the ALP activity was about 375.8u / g protein.
[0030] Embodiment 1:
[0031] 1) First, weave PLGA fiber cylinder materials with different diameter gradients (the minimum diameter is 3 mm, the maximum is 19 mm, the interval is 4 mm, and the number is 5);
[0032] 2) An in-situ mineralization process was used to mineralize hydroxyapatite on the surface of GO to obtain GO / HA nanofillers, wherein the mineralization solution was: 50 mM sodium chloride, 30 mM disodium hydrogen phosphate, 100 mM potassium chloride, 5 mM potassium hydrogen phosphate, 0.6 mM magnesium sulfate, 0.9 mM magnesium chloride, 5 mM calcium chloride, 0.2 mM sodium bicarbonate, 0.4 mM dicalcium hydrogen phosphate, 0.05 mM sodium sulfate, 18 mM HEPES, and the solvent was deionized water; the mineralization temperature was 37 ° C, the mineralization time was 3 days, and the stirring rate was 30 r / min. At the same time, a freeze-explosion method was used (the solution was stirred and swollen for 30 minutes, then frozen at -20°C, and then ice was chiseled until the ice was completely melted, and the above process was repeated 4 times) to prepare an alkali-soluble chitosan / cellulose mixed solution composited with GO / HA (chitosan 4wt%, cellulose 4wt%, GO / HA 0.8wt%, urea 6wt%, lithium hydroxide monohydrate 8wt%, and the rest was deionized water, wherein the molecular weight of chitosan was 1 million, the degree of deacetylation was 80%, and the cellulose was 1.8 million), and low-speed centrifugation (speed of 1000rpm, time of 5min) was used for degassing;
[0033] 3) The upper and lower ends of the fiber cylinder are fixed on an open cylindrical mold (with a diameter of 2 cm and a height of 10 cm. A hook is provided on the lower end base for fixing the lower end of the fiber cylinder, and a bracket is provided on the upper end for fixing the upper end of the fiber cylinder). The above solution is poured onto the wall together with the mold and transferred to 60°C for in-situ gelation (the in-situ gelation time is 2 hours, and deionized water is added to the gel every 30 minutes during the gelation process);
[0034] 4) After the deionized water dialyzate is completely used, the material is transferred to a rotary drying device (the heating and drying assembly is composed of two parallel and counter-rotating heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying and dehydration (the screw speed is 30 r / min and the heating temperature is 60°C), and the desired high-strength nano-composite screw material is obtained after turning according to the drawing.
[0035] Compared with comparative example 1, this embodiment adds a concentric fiber tube structure. First, the extract of the above material was prepared. After co-culturing it with BMSCs for 7 days, the CCK-8 results showed that the cell survival rate was about 92.3%; the bending strength of the screw was about 426.5MPa. After co-culturing the material with BMSCs for 14 days, ALP was detected, and the results showed that the ALP activity was about 358.1u / g protein.
[0036] Embodiment 2:
[0037] 1) First, weave PLGA fiber cylinder materials with different diameter gradients (the minimum diameter is 3 mm, the maximum is 17 mm, the interval is 7 mm, and the number is 3);
[0038] 2) An in-situ mineralization process was used to mineralize hydroxyapatite on the surface of GO to obtain GO / HA nanofillers, wherein the mineralization solution was: 50 mM sodium chloride, 30 mM disodium hydrogen phosphate, 100 mM potassium chloride, 5 mM potassium hydrogen phosphate, 0.6 mM magnesium sulfate, 0.9 mM magnesium chloride, 5 mM calcium chloride, 0.2 mM sodium bicarbonate, 0.4 mM dicalcium hydrogen phosphate, 0.05 mM sodium sulfate, 18 mM HEPES, and the solvent was deionized water; the mineralization temperature was 37 ° C, the mineralization time was 3 days, and the stirring rate was 30 r / min. At the same time, a freeze-explosion method was used (the solution was stirred and swollen for 30 minutes, then frozen at -20°C, and then ice was chiseled until the ice was completely melted, and the above process was repeated 4 times) to prepare an alkali-soluble chitosan / cellulose mixed solution composited with GO / HA (chitosan 4wt%, cellulose 4wt%, GO / HA 0.8wt%, urea 6wt%, lithium hydroxide monohydrate 8wt%, and the rest was deionized water, wherein the molecular weight of chitosan was 1 million, the degree of deacetylation was 80%, and the cellulose was 1.8 million), and low-speed centrifugation (speed of 1000rpm, time of 5min) was used for degassing;
[0039] 3) The upper and lower ends of the fiber cylinder are fixed on an open cylindrical mold (with a diameter of 2 cm and a height of 10 cm. A hook is provided on the lower end base for fixing the lower end of the fiber cylinder, and a bracket is provided on the upper end for fixing the upper end of the fiber cylinder). The above solution is poured onto the wall together with the mold and transferred to 60°C for in-situ gelation (the in-situ gelation time is 2 hours, and deionized water is added to the gel every 30 minutes during the gelation process);
[0040] 4) After the deionized water dialyzate is completely used, the material is transferred to a rotary drying device (the heating and drying assembly is composed of two parallel and counter-rotating heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying and dehydration (the screw speed is 30 r / min and the heating temperature is 60°C), and the desired high-strength nano-composite screw material is obtained after turning according to the drawing.
[0041] Compared with Example 1, the number and density of PLGA fiber tubes were reduced in this example. First, the extract of the above material was prepared, and after co-culturing with BMSCs for 7 days, the CCK-8 results showed that the cell survival rate was about 90.6%; the bending strength of the screw was about 341.1MPa. After co-culturing the material with BMSCs for 14 days, ALP was detected, and the results showed that the ALP activity was about 325.6u / g protein.
[0042] Embodiment 3:
[0043] 1) First, weave PLGA fiber cylinder materials with different diameter gradients (the minimum diameter is 3 mm, the maximum is 19 mm, the interval is 4 mm, and the number is 5);
[0044] 2) An in-situ mineralization process was used to mineralize hydroxyapatite on the surface of GO to obtain GO / HA nanofiller, wherein the mineralization solution was: 50 mM sodium chloride, 30 mM disodium hydrogen phosphate, 100 mM potassium chloride, 5 mM potassium hydrogen phosphate, 0.6 mM magnesium sulfate, 0.9 mM magnesium chloride, 5 mM calcium chloride, 0.2 mM sodium bicarbonate, 0.4 mM dicalcium hydrogen phosphate, 0.05 mM sodium sulfate, 18 mM HEPES, and the solvent was deionized water; the mineralization temperature was 37 ° C, the mineralization time was 7 days, and the stirring rate was 30 r / min. At the same time, a freeze-explosion method was used (the solution was stirred and swollen for 30 minutes, then frozen at -20°C, and then ice was chiseled until the ice was completely melted, and the above process was repeated 4 times) to prepare an alkali-soluble chitosan / cellulose mixed solution composited with GO / HA (chitosan 4wt%, cellulose 4wt%, GO / HA 8wt%, urea 6wt%, lithium hydroxide monohydrate 8wt%, and the rest was deionized water, wherein the molecular weight of chitosan was 1 million, the degree of deacetylation was 80%, and the cellulose was 1.8 million), and low-speed centrifugation (speed of 1000rpm, time of 5min) was used for degassing;
[0045] 3) The upper and lower ends of the fiber cylinder are fixed on an open cylindrical mold (with a diameter of 2 cm and a height of 10 cm. A hook is provided on the lower end base for fixing the lower end of the fiber cylinder, and a bracket is provided on the upper end for fixing the upper end of the fiber cylinder). The above solution is poured onto the wall together with the mold and transferred to 60°C for in-situ gelation (the in-situ gelation time is 2 hours, and deionized water is added to the gel every 30 minutes during the gelation process);
[0046] 4) After the deionized water dialyzate is completely used, the material is transferred to a rotary drying device (the heating and drying assembly is composed of two parallel and counter-rotating heating screws, and the two screw bodies are provided with stainless steel cylinders with fine holes) for drying and dehydration (the screw speed is 30 r / min and the heating temperature is 60°C), and the desired high-strength nano-composite screw material is obtained after turning according to the drawing.
[0047] Compared with Example 1, this example increases the mineralization time of GO / HA and the amount of GO / HA added to the polymer solution. First, the extract of the above material was prepared and co-cultured with BMSCs for 7 days. The CCK-8 results showed that the cell survival rate was about 88.6%; the bending strength of the screw was about 453.5MPa. After the material was co-cultured with BMSCs for 14 days, ALP was detected, and the results showed that the ALP activity was about 424.2u / g protein.
Claims
1. A method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure, characterized in that: The following steps are involved: 1) firstly weave polylactic acid-co-glycolic acid (PLGA) fiber cylindrical materials with different diameter gradients; 2) using an in-situ mineralization process to mineralize hydroxyapatite on the surface of graphene oxide (GO) to obtain GO / HA nanofillers, and using a freeze-blasting method to prepare an alkali-soluble chitosan / cellulose mixed solution composited with GO / HA, and degassing by low-speed centrifugation; 3) Fiber cylinders of different diameters are concentrically placed and fixed in open cylindrical molds respectively, the above solution is poured against the wall, and the molds are transferred together to 60-80°C for in-situ gelation; 4) After dialysis, the material is transferred to a rotary drying device for drying and dehydration, and the desired high-strength nano-composite screw material is obtained after turning according to the drawing.
2. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 1, characterized in that: In step 1), the diameter of the fiber cylinder is 3-49 mm, and the fiber cylinders are arranged at equal intervals from small to large, and the number of the fiber cylinders is 3-15.
3. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 1, characterized in that: The in-situ mineralization process in step 2) is to add GO to the surface mineralization solution, wherein the diameter of GO is 3-6 microns and the concentration is 0.01-0.08wt%; the mineralization temperature is 35-37°C, the mineralization time is 1-7 days, and the stirring rate is 30-60r / min.
4. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 3, characterized in that: The surface mineralization solution has a formula of: 50-70 mM sodium chloride, 20-30 mM disodium hydrogen phosphate, 60-100 mM potassium chloride, 5-10 mM potassium hydrogen phosphate, 0.4-0.75 mM magnesium sulfate, 0.8-1.2 mM magnesium chloride, 4-6 mM calcium chloride, 0.2-0.4 mM sodium bicarbonate, 0.4-0.6 mM dicalcium hydrogen phosphate, 0.025-0.05 mM sodium sulfate, 13-25 mM HEPES, and the solvent is deionized water.
5. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 1, characterized in that: The freezing-explosion method is to stir and swell the alkali-soluble chitosan / cellulose solution containing GO / HA nanofillers for 30-60 minutes, freeze it at -20--80°C, and then chip the ice until the ice is completely melted. The above process is repeated 3-5 times to obtain a completely dissolved alkali-soluble chitosan / cellulose mixed solution.
6. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 5, characterized in that: The alkali-soluble chitosan / cellulose solution has a formula of: a total concentration of chitosan and cellulose of 4-10wt%, GO / HA of 0.5-10wt%, urea of 5-7wt%, lithium hydroxide monohydrate of 7-10wt%, and the rest of deionized water, wherein the molecular weight of chitosan is 1-2 million, the degree of deacetylation is 70-80%, and the cellulose is 1-2 million.
7. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 1, characterized in that: The low-speed centrifugal degassing process is: the speed is 1000-1500rpm, and the time is 5-15min.
8. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 1, characterized in that: In step 3), the diameter of the open cylindrical mold is 2-5 cm and the height is 5-10 cm; the in-situ gelation time is 1-3 h, and deionized water is added to the gel at intervals of 30 min during the gelation process.
9. The method for preparing a high-strength nanocomposite screw material based on a concentric fiber tube structure according to claim 1, characterized in that: The structure of the rotary drying equipment in step 4) is as follows: the heating and drying component is two parallel and juxtaposed heating screws that can rotate in opposite directions. A stainless steel cylinder with fine holes is placed above the two screws for placing the sample to be dried. The screw speed is 20-50r / min and the heating temperature is 50-80°C.
10. A high-strength nanocomposite screw material based on a concentric fiber tube structure, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite polyether-ether-ketone material as well as preparation method and application thereof
CN113583406A
Bioactive implantable devices and composite biomaterials and methods for manufacturing bioactive implantable devices and composite biomaterials
CN115297907A
High-strength degradable composite material with concentric wood-like annual ring structure as well as preparation method and application of high-strength degradable composite material
CN117958939A
Bio-composites of hydroxyapatite / carboxymethyl cellulose / gelatin and hydroxyapatite / carboxymethyl cellulose / chitosan / gelatin with bone like load bearing properties
IN201721009554A
A biocomposite of biomineralized graphene oxide and its use for bone tissue engineering
US20180214599A1